2012
DOI: 10.1111/j.1744-1633.2012.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic spleen‐preserving distal pancreatectomy: A consecutive series at an experienced centre

Abstract: Aim The increasing experience within the area of laparoscopic procedures has paved the way for technically‐complex procedures, such as distal pancreatectomy. In order to avoid complications associated with concomitant splenectomy, these procedures are increasingly performed with spleen preservation. A drawback is the low number of cases, which does not allow for an evidence‐based comparison between laparoscopic and open procedures, and spleen‐preserving and concomitant splenectomy procedures. Patients and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Hence, we conclude that smaller lesson is more suitable for LSPDP but size did not influence the choice of laparoscopy or open approach in overall distal pancreatectomies. This agrees with some recent studies [28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Hence, we conclude that smaller lesson is more suitable for LSPDP but size did not influence the choice of laparoscopy or open approach in overall distal pancreatectomies. This agrees with some recent studies [28].…”
Section: Discussionsupporting
confidence: 94%
“…Other studies showed a trend of reduced hospital stay (non significant) in laparoscopic spleen preservation group like our study. However, no study has compared four separate arms together as we have done [28].…”
Section: Discussionmentioning
confidence: 99%